Angiography vs physiology-based deferral of revascularization in patients with reduced left ventricular ejection fraction: a 10-year clinical follow-up. (14th October 2021) - Gallinoro, E; Paolisso, P; Bermpeis, K; Peregrina, E F; Candreva, A; Esposito, G; Fabbricatore, D; Sonck, J; Di Gioia, G; Vanderheyden, M; Bartunek, J; Collet, C; et al.
Abstract: Background: Deferring percutaneous coronary intervention (PCI) in patients with non-ischemic coronary stenoses based on fractional flow reserve (FFR) and preserved left ventricular ejection fraction (LVEF) is associated with favorable long-term clinical outcomes. In patients with reduced LVEF, the role of reversible/residual ischemia in deferring revascularization is still debated. Purpose: To investigate whether FFR provides additive clinical benefit compared to coronary angiography in deferring revascularization in patients with intermediate coronary stenoses and reduced LVEF. Methods: Among 4577 coronary angiographies performed between 2002 and 2010, consecutive patients with reduced LVEF (≤50%) and at least one intermediate coronary stenosis [diameter stenosis (DS)% 40–70%] in whom revascularization was deferred based either on FFR (FFR-guided) or angiography (Angiography-guided) were screened. The primary endpoint of the study was cumulative incidence of death at 10 years. Results: A total of 843 patients were included (209 in the FFR-guided and 634 in the Angio-guided group). Median clinical follow-up was 7.1 years (IQR 3.2–11.2 years). After 1:1 propensity score matching, baseline characteristics between the two groups were similar. All-cause death at 10 years was significantly lower in the FFR-guided compared with the Angiography-guided group (94 [45%] vs 115 [55%], HR 0.72 [95% CI 0.55–0.95], p<0.05). Similarly, the incidence of major adverse cardiovascular and cerebrovascular events (MACCE, composite of all-cause death, myocardial infarction, any revascularization and stroke) was lower in the FFR guided group (125 [60%] vs 140 [67%], HR 0.77 [95% CI 0.61–0.98], p<0.05). Conclusions: In patients with reduced LVEF and associated coronary artery disease, deferring revascularization of intermediate stenoses based on FFR is associated with lower incidence of death and MACCE at 10 years. FUNDunding Acknowledgement: Type of funding sources: None.